(untitled) (Torani Journal of Fisheries and Marine Science, 2017)
The research aim is to know the diversity of coral fish in Badi and Kodingareng Lompo islands. The study is held from May until June 2014. The samples are taken twice for one month by using belt transect method. Transect lines were put on depth 3 meters and each dept was. The observed region is as long 50-meter transect lines with the shoreline margin 2,5 meter at the left and right side of the transect. Analysis of data is done by calculating the kinds of compositions, abundance, diversity index, uniformity, and domination. The result of this research is the composition of coral fish in each island. In Badi islands the composition of coral fish is 50 kinds of fish from 15 families with 131 fish. In Kodingareng Lompo island, the composition of coral fish is 21 kinds of fish from 9 families with 82 fish. In Badi island , the diversity index is 3.3870 and Kodingareng Lompo island is 2.5566, the uniformity index Badi island is 0.2606 and Kodingareng Lompo island is 0.2527, and the dominantion index Badi island is 0.0461 and Kodingareng Lompo island is 0.0967. Keywords: Diversity, Abundance, Coral fish, Badi island, Kodingareng Lompo island